2019
DOI: 10.33371/ijoc.v13i2.621
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity and Reliability of Indonesian Version of RAND SF-36 Quality of Life Questionnaire in Breast Cancer Patients

Abstract: Background: The number of breast cancer patients in Indonesia is increasing but there are still only a few researches that assess their quality of life. RAND SF-36 is a quality of life instrument that is widely used. In Indonesia, the validity and reliability of the instrument is still under development, especially in breast cancer patients. Various health status questionnaires have been used in physical rehabilitation studies involving patient with pacemaker, but for women with breast cancer, the usefulness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Based on validity analysis results all of the questions have a significant value <0.001 which indicates that all of the questions are valid. Reliability results also give Cronbach's Alpha value 0,738 (>0,6) so the conclusion shows that the questions are reliable and consistent to measure the mental health domain of healthcare workers [16][17][18] The SF domain wants to see the extent of the impact of physical health or emotional problems on someone's social activities on the past 4 weeks, these social activities are general social activities with family, friends, neighbors or groups and social activities like visiting friends, relatives, etc. The social functioning domain of the SF 36 questionnaire consists of 2 questions.…”
Section: Validity and Reliability Testingmentioning
confidence: 82%
See 3 more Smart Citations
“…Based on validity analysis results all of the questions have a significant value <0.001 which indicates that all of the questions are valid. Reliability results also give Cronbach's Alpha value 0,738 (>0,6) so the conclusion shows that the questions are reliable and consistent to measure the mental health domain of healthcare workers [16][17][18] The SF domain wants to see the extent of the impact of physical health or emotional problems on someone's social activities on the past 4 weeks, these social activities are general social activities with family, friends, neighbors or groups and social activities like visiting friends, relatives, etc. The social functioning domain of the SF 36 questionnaire consists of 2 questions.…”
Section: Validity and Reliability Testingmentioning
confidence: 82%
“…In the conclusion for validity and reliability, the physical functioning domain consists of 9 valid questions and 1 non-valid question. After we deleted the non-valid question we conducted the reliability analysis and the results showed that Cronbach's alpha value is 0,767 (>0,6) which is indicated that the 9 questions to measure the PF domain of healthcare workers is valid and reliable [16][17][18] The RP domain consists of 4 questions. The translating questions to measure role physical in Indonesian version can we described as "do you had difficulty to spend all of your time to do some work or other activities?…”
Section: Validity and Reliability Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Validity and reliability test had been done previously and it is eligible to use for assessing patients' satisfaction level after fibroadenoma surgery. There are numerous types of questionnaire to assess the quality of life of breast cancer patients, such as RAND SF-36 that had been validated in Indonesian version (Ramadhanty et al, 2019). However, there is no questionnaire yet to assess fibroadenoma patient's satisfaction level after surgery (Putra et al, 2020).…”
Section: Patient Satisfactionmentioning
confidence: 99%